Cherishing the Body: Embodiment and the Intersubjective World in Michèle Roberts’s Playing Sardines - Goszczyńska, Marta (The Woman Artist: Essays in memory of Dorota Filipczak, 2024)
The essay sets out to analyze selected stories from Michèle Roberts’s 2001 collection, Playing Sardines, in the light of theories of embodiment. Opposing the Cartesian body/mind dualism, these theories refuse to view the body merely as an object or an imperfect instrument over which the mind must exercise control. Instead, they insist on recognizing the embodied character of human experience by portraying the body as intricately engaged with the surrounding world. As I will demonstrate, these views find their reflection in Roberts’s fiction, whose purpose has always been, as she declares, “to rescue the body and cherish it and love it and touch it and smell it and make it into language” (“January”). This self-appointed project seems to me to be consistent with the approach of embodiment theorists, who also “rescue” the reputation of the body by identifying it as an ethically productive locus of intersubjectivity. My argument in the essay will be threefold. First of all, I will discuss Roberts’s stories as sharing with the philosophies of embodiment their skepticism towards the Cartesian body/mind dualism. In particular, I will focus on stories depicting the negative consequences of privileging the mind over the body, a stance that Sonia Kruks identifies as leading to what she refers to as “antagonistic intersubjectivity” (39–42). In the second part, I will move on to discuss scenes dramatizing the moment of liberation, granted to many of Roberts’s characters as they break free from damaging interpersonal relationships and/or move towards more positive interactions with others. Finally, in the third part of the essay, I will consider these positive, mutually affirmative experiences of intersubjectivity.